The G/G Genotype of a Resistin Single-Nucleotide Polymorphism at −420 Increases Type 2 Diabetes Mellitus Susceptibility by Inducing Promoter Activity through Specific Binding of Sp1/3 - Osawa, Haruhiko; Yamada, Kazuya; Onuma, Hiroshi; Murakami, Akiko; Ochi, Masaaki; Kawata, Hiroko; Nishimiya, Tatsuya; Niiya, Toshiyuki; Shimizu, Ikki; Nishida, Wataru; Hashiramoto, Mitsuru; Kanatsuka, Azuma; et al. (American journal of human genetics, 2004)
Insulin resistance is a major cause of type 2 diabetes mellitus (T2DM). Resistin, an adipocyte-secreted hormone, antagonizes insulin. Transgenic mice that overexpress the resistin gene ( Retn) in adipose tissue are insulin-resistant, whereas Retn (−/−) mice show lower fasting blood glucose, suggesting that the altered Retn promoter function could cause diabetes. To determine the role of RETN in human T2DM, we analyzed polymorphisms in its 5′ flanking region. We found that the −420G/G genotype was associated with T2DM (397 cases and 406 controls) ( P=.008; adjusted odds ratio = 1.97 [by logistic regression analysis]) and could accelerate the onset of disease by 4.9 years ( P=.006 [by multiple regression analysis]). Meta-analysis of 1,888 cases and 1,648 controls confirmed this association ( P=.013). Linkage disequilibrium analysis revealed that the −420G/G genotype itself was a primary variant determining T2DM susceptibility. Functionally, Sp1 and Sp3 transcription factors bound specifically to the susceptible DNA element that included −420G. Overexpression of Sp1 or Sp3 enhanced RETN promoter activity with −420G in Drosophila Schneider line 2 cells that lacked endogenous Sp family members. Consistent with these findings, fasting serum resistin levels were higher in subjects with T2DM who carried the −420G/G genotype. Therefore, the specific recognition of −420G by Sp1/3 increases RETN promoter activity, leading to enhanced serum resistin levels, thereby inducing human T2DM.